2006
DOI: 10.1200/jco.2006.06.6126
|View full text |Cite
|
Sign up to set email alerts
|

Response and Resistance in a Non–Small-Cell Lung Cancer Patient With an Epidermal Growth Factor Receptor Mutation and Leptomeningeal Metastases Treated With High-Dose Gefitinib

Abstract: HIV and human papillomavirus (HPV) coinfected patients are at high risk of developing precancerous anal lesions (anal intraepithelial neoplasia) and anal malignancies. 1 The natural history (that is, progression and persistence) of HPV-associated lesions is accelerated by HIV-related immunosuppression, which may result in the reactivation of previously acquired HPV infection and loss of control of HPV viral replication. 2 The longer life expectancy of these coinfected patients in the era of HAART provides an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
181
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(188 citation statements)
references
References 10 publications
5
181
1
1
Order By: Relevance
“…This drug level would be grossly insufficient to inhibit the phosphorylation and activation of H870R+L858R double mutant as shown in this study. Although some clinical reports have shown that small molecule EGFR tyrosine kinase inhibitor can pass through the blood-brain barrier and cause shrinkage of brain metastasis (23)(24)(25)(26), other reports have suggested that tyrosine kinase inhibitor penetration into the brain could be incomplete (5,22), and brain metastasis was strongly associated with the emergence of acquired resistance in NSCLC patients treated with gefitinib (27). As shown in Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This drug level would be grossly insufficient to inhibit the phosphorylation and activation of H870R+L858R double mutant as shown in this study. Although some clinical reports have shown that small molecule EGFR tyrosine kinase inhibitor can pass through the blood-brain barrier and cause shrinkage of brain metastasis (23)(24)(25)(26), other reports have suggested that tyrosine kinase inhibitor penetration into the brain could be incomplete (5,22), and brain metastasis was strongly associated with the emergence of acquired resistance in NSCLC patients treated with gefitinib (27). As shown in Fig.…”
Section: Discussionmentioning
confidence: 94%
“…According to our results, this drug level could be marginally sufficient for controlling tumor cells in the lung. However, the gefitinib drug concentration attainable in the cerebrospinal fluid could be as low as 18 nmol/L for an oral dose of 500 mg/d and 42 nmol/L for 1,000 mg/d (22). This drug level would be grossly insufficient to inhibit the phosphorylation and activation of H870R+L858R double mutant as shown in this study.…”
Section: Discussionmentioning
confidence: 94%
“…With the concept of the disruption of blood brain barrier (BBB) by BM and radiation therapy, gefitinib with small molecular weight may have the ability to penetrate the BBB (Fidler et al, 2002;Van et al, 2002;Jackman et al, 2006). Furthermore, gefitinib might enhance radiosensitivity (Bianco et al, 2002;Huang et al, 2002;Bonner et al, 2006;Shimato et al, 2006;Das et al, 2007;Park et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms had improved and no cancer cells were detected. Jackman DM et al [6] found the 50% inhibitory concentration (IC 50 ) of gefi tinib in a cancer cell line obtained from the pleural effusion of a patient with EGFR gene exon 19 deletions who developed brain metastasis during oral gefi tinib (250 mg) treatment to be 10-50 nmol/L. Then they compared the gefi tinib concentration in the CSF with the gefi tinib dosage.…”
Section: Discussionmentioning
confidence: 99%